Revisiting conceptions, history, events and themes of health-promoting universities - Xavier, Samyra Paula Lustoza; Pinheiro, Maria Tainara; Reis, Gabriely Ferreira dos; Lima, Amanda Ferreira; Lima, Nathaly Almeida de; Nunes, Sabrina Freitas; Pereira, Emanuelly Vieira; Fialho, Ana Virginia de Melo; Machado, Maria de Fátima Antero Sousa; Miranda, Karla Corrêa Lima (Seven Editora, 2024)
Health Promotion (PrS) is a theme that has been increasingly popularized and expanded in social circles and, especially, in health. Since the First International Conference on PrS, held in Ottawa, Canada, in 1986, basic health requirements have been discussed, such as: peace, housing, education, food, income, stable ecosystem, sustainable resources, social justice and equity. DOI:https://doi.org/10.56238/sevened2024.001-063